Evaluation of the diagnostic yield of lung cancer on various Bronchoscopic modalities - K.C, Rajesh; Maharjan, Swojay; Shrestha, Kushal; Sedhain, Shashwot; Adhikari, Gopal; Maharjan, Sirapa; Panta, Chiranjibi; Basnet, Ashok; Basnet, Bina; Karmacharya, Kavita (Nepalese Respiratory Journal, 2024)
Introduction: Lung cancer is responsible for a major portion of cancer-related mortality worldwide, despite advancements in diagnostic technologies and treatment modalities. Bronchoscopy plays a central role in the diagnosis of lung cancer by allowing direct visualization of the airways and facilitating tissue sample collection through endobronchial brush, endobronchial wash, and endobronchial biopsy. Objective: To analyze the histomorphological patterns of lung malignancies and compare the diagnostic efficacy of different bronchoscopic techniques, like specifically bronchial wash cytology, endobronchial brush cytology, and endobronchial biopsy. Methods: A retrospective analysis of fiberoptic bronchoscopy (FOB) morphological findings, including bronchial wash and endobronchial brush cytology and endobronchial biopsy, was conducted in 78 patients aged 18 years and older with findings suspicious for malignancy on CT scan. Frequencies of various histopathological subtypes of lung cancer were tallied with the different diagnostic procedures and corresponding FOB findings. Diagnostic accuracy, sensitivity, and specificity of endobronchial brush cytology and bronchial wash cytology, both individually and in combination, were evaluated using biopsy as the reference standard. Associations between demographic variables, tumor and nodal staging, and bronchoscopic findings were also assessed. Results: Of the 78 patients, 63 (80.8%) had a confirmed diagnosis of malignancy on biopsy. The most frequently identified histopathological subtypes of lung cancer were squamous cell carcinoma (47.4%), followed by non- small cell lung carcinoma, not otherwise specified (14.1%), and small cell carcinoma (10.3%). On FOB, the tumors most frequently appeared as endobronchial growths (68.3%), followed by areas of unhealthy mucosa (55.6%) and polyploidal lesions (19%). Endobronchial brush cytology yielded a sensitivity of 49.2%, a specificity of 60%, and an overall diagnostic accuracy of 51.28%. In comparison, endobronchial wash cytology showed lower sensitivity (12.7%), higher specificity (86.7%), and a reduced diagnostic accuracy of 26.92%. When combined, these cytological methods yielded a sensitivity of 55.65%, a specificity of 52.02%, and a diagnostic accuracy of 54.4%. There was no significant association between clinical or bronchoscopic variables and malignancy status. Conclusions: The study reinforces the critical diagnostic role of bronchoscopic modalities in detecting pulmonary malignancies. The combination of endobronchial brush and bronchial wash cytology marginally improved sensitivity but with moderate specificity. The relatively low sensitivity of cytological techniques, especially endobronchial wash, highlights their limitations as standalone diagnostic tools.